Efforts to Improve Descriptive Writing Skills Using Realia Media in Grade V - Heriyawan Hutagalung; Izmawal Pebriani Nasution; Mastari Ramadhani; Mulkan Andika Situmorang; M. Mahdi Alatas (CV. Edujavare Publishing, 2026)
This study was motivated by the low descriptive writing skills of fifth-grade elementary school students, characterized by limited student participation, low motivation, and difficulties in expressing ideas in written form. The purpose of this study was to improve students’ descriptive essay writing skills through the use of realia media in Grade V of SDN JUNTI 2. This research employed a Classroom Action Research (CAR) design conducted in three cycles consisting of planning, action, observation, and reflection stages. The participants of the study were 29 fifth-grade students. Data were collected through observation, writing tests, and documentation, then analyzed descriptively to determine improvements in learning outcomes and classroom activities. The results revealed a significant improvement in students’ descriptive writing abilities in each cycle. The average student score increased from 5.89 in Cycle I to 6.41 in Cycle II and reached 8.00 in Cycle III. Student participation, motivation, and creativity in the learning process also improved through direct interaction with real objects. The findings indicate that the implementation of realia media effectively enhances students’ descriptive writing skills and creates more active and meaningful learning experiences. This study contributes to the development of innovative language learning strategies, particularly in improving elementary students’ writing competence through contextual and concrete instructional media.